(untitled) (Research, Society and Development, 2022)
This study aims to report the experience of teaching meditation online as a practice that promotes mental health during the social isolation of the COVID-19 pandemic. This is an experience report on one of the activities developed by the Extension Project for Mental Health Promotion Strategies at Universidade Federal Fluminense. Due to the COVID-19 pandemic, actions have been carried out remotely, in this case, meditation. Two cycles of Abundance meditation and two cycles of Ho’oponopono, with 21 days in each cycle, were performed. The abundance meditation activities were attended by 225 people, and the Ho’oponopono activities were attended by 357 people. Feedback from participants about the experience brought the perception of improvement in anxiety and fear of contamination by COVID-19, in addition to deep learning focused on self-knowledge. It was possible to conclude that meditation is a relevant resource for promoting mental health, especially in periods of social distance.